The start of the transplant journey: Referral for pediatric solid organ transplantation. (20th January 2014) - Shellmer, Diana; Brosig, Cheryl; Wray, Jo
Abstract The focus of the majority of the psychosocial transplant literature is on post‐transplant outcomes, but the transplant journey starts much earlier than this, at the point when transplantation is first considered and a referral for transplant evaluation is made. In this review, we cover information regarding the meaning of the referral process for solid organ transplantation. We discuss various factors of the referral for transplantation including the impact of referral on the pediatric patient and the family, potential expectations and misconceptions held by pediatric patients and parents, the role of health literacy, decision‐making factors, and the informational needs of pediatric patients and parents. We elucidate steps that providers can take to enhance transplant referral and provide suggestions for much needed research within this area.